A broadscale analysis of host‐symbiont cophylogeny reveals the drivers of phylogenetic congruence. (14th May 2021) - Hayward, Alexander; Poulin, Robert; Nakagawa, Shinichi
Abstract: Symbioses exert substantial biological influence, with great evolutionary and ecological relevance for disease, major evolutionary transitions, and the structure and function of ecological communities. Yet, much remains unknown about the patterns and processes that characterise symbioses. A major unanswered question is the extent to which symbiont phylogenies mirror those of their hosts and if patterns differ for parasites and mutualists. Addressing this question offers fundamental insights into evolutionary processes, such as whether symbionts typically codiverge with their hosts or if diversity is generated via host switches. Here, we perform a meta‐analysis of host‐symbiont phylogenetic congruence, encompassing 212 host‐symbiont cophylogenetic studies that include 10, 000 species. Our analysis supersedes previous qualitative assessments by utilising a quantitative framework. We show that symbiont phylogeny broadly reflects host phylogeny across biodiversity and life‐history, demonstrating a general pattern of phylogenetic congruence in host‐symbiont interactions. We reveal two key aspects of symbiont life‐history that promote closer ties between hosts and symbionts: vertical transmission and mutualism. Mode of symbiosis and mode of transmission are intimately interlinked, but vertical transmission is the dominant factor. Given the pervasiveness of symbioses, these findings provide important insights into the processes responsible for generating and maintaining the Earth's rich biodiversity. Abstract : Symbioses exert substantial biological influence, yet a major unanswered question is the extent to which symbiont phylogenies mirror those of their hosts and if patterns differ for parasites and mutualists. We utilise a quantitative framework to investigate host‐symbiont phylogenetic congruence, by performing a meta‐analysis encompassing 212 host‐symbiont cophylogenetic studies that include 10, 000 species. We find that symbiont phylogeny broadly reflects host phylogeny across biodiversity and life‐history, and demonstrate that two aspects of symbiont life‐history promote closer ties between hosts and symbionts, vertical transmission and mutualism, with vertical transmission emerging as the dominant factor.